MOHS MICROGRAPHIC SURGERY FOR BASAL CELL CARCINOMA: A REVIEW OF TREATMENT RESULTS - Nguyen Hong, Son; Le Van, Duc; Pham Ngan, Giang; Vu Nguyen, Binh; Nguyen Dinh, Quan; Nguyen Huu, Quang; Vu Dinh, Tam; Nguyen Canh, Tung; Le Thi Thanh, Hien (Tạp chí Da liễu học Việt Nam, 2024)
Objectives: To evaluate the results of Mohs Micrography Surgery (MMS) in the treatment of basal cell carcinoma (BCC). Materials and methods: We used the database of PUBMED and EMBASE to evaluate the results of MMS in treatment of BCC. Results: Nine studies with the total number of 5845 BCC cases were included in this review, the follow-up time varied from 12 to 42 months. The overall cumulative probabilities of recurrence after MMS were 2.4%. The cumulative probability of recurrence for the primary BCC group and the recurrent BCC group was 2.9% and 7.2%, respectively. In the recurrent BCC group, the cumulative probability of recurrence after MMS was lower than after standard surgical excision (SSE) (3.9% vs 13.5%, p < 0.05). In MMS group, 52% of patients required one round of excision to achieve complete removal of BCC, 34% needed two rounds and 14% needed three rounds. The size of final skin defect after MMS was 1.34 times larger than that of the primary tumor (p < 0.05). Conclusion: MMS is superior to SSE in BCC treatment, with lower recurrence rate and better normal skin-sparing. Therefore, MMS is strongly recommended for surgical treatment of BCC, especially in high-risk BCC. Received 28 June 2023 Revised 26 September 2023 Accepted 29 November 2023